Seed management on agricultural research farms - Claassen, S.L. (1995)
Seed processing and storage are important components in transforming the effort of breeders into improved crops for farmers. Seed processing includes drying, removal of contaminants, size grading, and treatment with specific materials. Storage aims at keeping seed in good condition until the next planting season. A variety of equipment and methods is available for seed processing and storage.